Istilah-Istilah Wanita dalam al-Quran dan al-Sunnah - Hj Ismail, Paizah (Jurnal Usuluddin, 1997)
The article gives a special emphasis to the Terminology of women in al-Quran and al-Sunnah, al-Untha, al-Marah and al-Nisa which are quoted in al-Quran and al-Sunnah.